Quest Myth in Devkota’s Narratives: A Study of Muna Madan - Gautam, Mani Bhadra (Cognition, 2019)
The Quest Myth centers on transformation of consciousness, the hero’s journey, human feelings, understanding, observation, actions, experiences, life and death. It undergoes on archetypal and spiritual growth of the time derived themes and ideas from a long standing, scenarios/socio-historical context. Primitive mental images inherited from the earliest human ancestors in Jungian theory are reflected in Laxmi Prasad Devkota’s Muna Madan. It captures the mythical images and presents events relating with human feelings and thoughts in Jungian, Kallis, Kapell and Izod’ framework. It subjectivizes on human cruelty, socio-cultural violence and dis-harmony representing the past reality and present changes as narrated in the text. This article presents a brief sketch of Devkota’s orientation to mythical world. I have tried to examine the narratives in Muna Madan from mythical perspectives.